Factors affecting adoption of digital payments by semi-rural Indian women: extension of UTAUT-2 with self-determination theory and perceived credibility. Issue 6 (31st August 2021) - Manrai, Rishi; Goel, Utkarsh; Yadav, Prashant Dev
Abstract : Purpose: The aim of this research is to investigate the factors influencing the adoption of digital payments by the semi-rural women in India. Design/methodology/approach: The study extended the factors of unified theory of acceptance and use of technology UTAUT-2, with perceived credibility and self-determination theory to understand the use behaviour of the rural Indian women. The study checked the mediating role of some constructs besides testing the direct relationship. The study was conducted in the rural parts of the adjoining areas of Delhi, where the women from different states, education and financial background live. The research model was empirically tested on 568 respondents using structural equation modelling (SEM) technique. Findings: The research model was able to explain 72.6% variance in the user behaviour variable. Effort expectancy, habit, facilitating conditions as well as perceived competence emerged out to be significant determinants of use behaviour. Besides these direct relationships, two constructs, habit as well as facilitating conditions were found to partially mediate the relationship between behavioural intention and behaviour. Originality/value: This study provides some very critical clues for the companies providing digital payment services, by highlighting the significant factors explaining the technology adoption by semi-rural women. The companies must devise suitable marketing strategies to inculcate trust in mind of perspective customers towards their companies as well as the service provided by them. The role of simple digital platform, that is easy to learn and use, is also an important element in determining the technology adoption.